Competencies on sustainability and blue entrepreneurship in university guides: the challenge of a truly blue economy - Fernández-Jiménez, Miguel Ángel; Aranda-Garrido, María Lourdes; Mena-Rodríguez, Esther (Taylor & Francis, 2025)
The inclusion of competences related to sustainability and blue entrepreneurship aligns with the 2030 Agenda, a global framework adopted by the United Nations to promote sustainability through 17 Sustainable Development Goals (SDGs). Universities, as agents of change, must address socio-environmental problems through research, education, innovation, collaboration, and sustainable practices, aiming for a positive societal and environmental impact. Through an R&D&I pro ject under the Andalusian Plan for Research, Development, and Innovation con ducted a study to diagnose the extent to which these competences are included in the teaching programs of nine Andalusian public universities. Using a mixed methodology, the study involved 22 teachers and analyzed 81 programs from 40 university degrees. Results show statistically significant differences by university and branch of knowledge, with Science and Engineering and Architecture incor porating these competences more extensively. The study indicates that sustain ability is unevenly developed across universities, necessitating a review and modernization of study programs to meet the objectives of the Entrepreneurship Plan by the Conference of Rectors of Spanish Universities.
Keywords: Ecología social; Desarrollo sostenible; Competencies in sustainability; Blue entrepreneurship; Higher education; Sustainable Development Goals